Fruit set and yield of ‘Santa Maria’ and ‘Abate Fetel’ pears are increased by early spring application of aminoethoxyvinilglycine (AVG) (Revista de Ciências Agroveterinárias, 2018)
The objective of this study was to evaluate the effect of aminoethoxyvinilglycine (AVG), sprayed at different doses, on yield components and fruit quality of pear trees, during the growing seasons of 2015/2016 and 2016/2017, in São Joaquim, Santa Catarina state, Brazil. Treatments consisted of AVG sprayed one week after full bloom (WAFB) ) at different doses on ‘Santa Maria’ (0 mg L-1, 40 mg L-1, 80 mg L-1, and 120 mg L-1) and ‘Abate Fetel’ (0 mg L-1, 80 mg L-1, and 100 mg L-1) pear trees, arranged in a randomized block design. Yield components and fruit quality attributes were assessed. Fruit set, number of fruit per tree and yield are significantly improved and positively related to AVG dose for both cultivars, while fruit quality attributes and fruit size are not affected by treatments.
Keywords: Pyrus communis; plant growth regulators; pyrus; fruit; efficiency